Setal Field Transects, Evolutionary Transitions and Gecko–Anole Convergence Provide Insights Into the Fundamentals of Form and Function of the Digital Adhesive System of Lizards - Russell, Anthony P.; Garner, Austin M. (Frontiers in Mechanical Engineering, 2021)
Recent years have witnessed a multitude of studies focusing on gekkotan adhesion. Intense interest in this phenomenon was triggered by the discovery of the manner and magnitude of the forces generated by the hair-like filaments (setae) on the toe pads and inspired the development of the next generation of smart, reversible synthetic adhesives. Most studies pursuing these goals have concentrated on the generalized form and properties of gekkotan setae outlined in those key early studies, resulting in the fabrication of synthetic filaments of uniform dimensions. Although there are over 1800 species of extant geckos, and hundreds of species of anoles (a separate lizard lineage that has convergently evolved adhesive toe pads), most investigations have used relatively few species as the source of basic information, the Tokay gecko (Gekko gecko) being the most prominent among these. Such exemplar taxa generally exhibit structurally intricate setae and morphologically complex configurations of the adhesive apparatus. Setal structure taken to be characteristic of these taxa is generally reported by singular statements of maximal length, diameter, density and branching pattern. Contemporaneous work focusing on the configuration of setae at locations across the toe pads and upon the evolutionary origin of adhesively competent digits in anoles and specific lineages of geckos, however, has revealed extensive variation of setal structure within individuals, information about how setae may have arisen from non-adhesive filamentous precursors, and how newly adhesively competent digits have been integrated into pre-existing patterns of locomotor mechanics and kinematics. Such observations provide insights into what is minimally necessary for adhesively competent digits to function and reveal the simplest configuration of components that make this possible. We contend that information gleaned from such studies will assist those seeking to employ the principles of fibrillar-based adhesion, as exemplified by lizards, for bio-inspired applications.